Market Reaction Differentiation to Share Buyback Announcements in Terms of Market Capitalization - Salsabila, Sapna; Nanda , Sahabuddin; Nurlina, Nurlina (Universitas Bangka Belitung, 2026)
This study aims to analyze the differences in market reactions to share buyback announcements in large-cap and small-cap companies listed on the Indonesia Stock Exchange during the period 2022–2024. Market reactions are measured through abnormal returns and trading volume activity (TVA) around the date of the buyback announcement. This study uses a comparative quantitative approach with the event study method. The research sample consists of 45 share buyback actions selected using purposive sampling. Abnormal returns were calculated using the Constant Return Model (CRM), while differences before and after the buyback announcement were analyzed using a paired sample t-test, as the test compares market conditions before the announcement (anticipation period) and after the announcement (adjustment period). The results show that both big cap and small cap companies experienced significant negative abnormal returns in the pre-announcement and post-announcement periods, but no significant abnormal returns were found on the announcement date. These findings indicate that the market had anticipated the buyback information prior to the official announcement. Meanwhile, trading volume activity (TVA) results show that big cap companies experienced significant and sustained changes in trading volume after the buyback announcement, while small cap companies did not show statistically significant changes in trading volume. Overall, the findings indicate that company size does not affect short-term stock price reactions, but influences differences in investor trading activity following share buyback announcements.